Dongli Lake Eco Info Park - Ottosson, Johanna (2017)
Dongli Lake is a lake situated in the northeast of Tianjin in China. In the ecologically sensitive area just north of Dongli Lake, a new urban development for around 70 000 people was constructed. Before the transformation the area consisted of wetland, and small-scale agricultural in the forms of fishponds and farming. The area was described as high in biodiversity such as bird-and insect life, thanks to its unique environment. In 2004 a conceptual master plan for the new urban development was compiled, within what came to be called ’the Dongli Lake project’. Within this master plan an ecological approach was used as one important aspect. The ecological approach focused on preserving much of the original structures of fishponds, wetland, and reed. The purpose was to retain the biodiversity of the site, and stay true to the character of the landscape. I visited the Dongli Lake project area in 2016, eleven years after the conceptual master plan was carried out. By then, most of the new district was already built and people had been moving in. During my visit, I interviewed some of the residents to find out what they knew about the ecological values on which their home district was largely constructed. From those interviews I got the impression that the ecological awareness in regard to the site was lacking among the residents. I identified the lacking awareness as a potential problem since knowledge among the habitants regarding a given site’s ecology, is a cornerstone in sustainable ecological design. Without ecological awareness among the residents, an ecological landscape project is extremely vulnerable to change that may inadvertently cause its failure. As a respond to the issue of lack in ecological awareness among the residents, I came up with the idea of designing an ecological information park connected to the area: The Dongli Lake Eco Info Park. The concept of the park was ’ecological knowledge spreading’. The park aimed to enhance ecological awareness with the long term goal of also fostering environmental care in regard to the site, targeting the local population.